Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMP Negeri 1 Pariaman - Mariza Inesti (Departemen Matematika, 2020)
Mathematical communication skills are one basic abilities that must be possessed by students. But in reality at class VIII SMPN 1 Pariaman are still low. The solution used to overcome these problems are Think Pair Share (TPS) learning model.. The purpose of the research was to describe whether the mathematical communication skills of Grade VIII students of SMP N 1 Pariaman that taught using TPS learning were better than students who using direct learning. The research type is quasi experiment with the design of Randomized Control-Group Only Design. The sample class was VIII2 as experimental class and VIII4 as control class. The instruments used to collect information in this research were final test and quizzes. Based on the test we can concluded that students who learn using TPS have mathematical communication skills better than students who taught using the direct learning model in class VIII at SMPN 1 Pariaman.Keywords — direct learning, mathematical communication skills, TPS learning model.